Analisis Pengaruh Stock Split Terhadap Volume Perdagangan, Harga Saham, dan Abnormal Return pada Perusahaan yang Terdaftar di BEI Periode 2017 - 2018 - Agus Amanda Tanoyo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This study aims to determine the difference in the trading volume activity, stock prices and abnormal returns before and after the announcement of a stock split. The population of this study are all companies listed in Indonesia Stock Exchange that take corporate action in the form of stock split at period 2017-2018. Sampling using purposive sampling. Based on the sampling criteria predetermined number of samples acquired 24 stocks. The analytical method used is the analysis Wilcoxon Signed Rank Test with the observation period (event window) is 14 days. The results showed that there were differences in the trading volume activity and stock prices before and after the announcement of stock split, while the last hypothesis showed that there were no differences in abnormal returns before and after the announcement of stock split.